Synthesis, Characterization, Antimicrobial, DNA Cleavage, and Antioxidant Studies of Some Metal Complexes Derived from Schiff Base Containing Indole and Quinoline Moieties - Mahendra Raj Karekal; Vivekanand Biradar; Mruthyunjayaswamy Bennikallu Hire Mathada (Bioinorganic Chemistry and Applications)
A new Schiff base of 5-chloro-3-phenyl-1H-indole-2-carboxyhydrazide and 3-formyl-2-hydroxy-1H-quinoline (HL), and its Cu(II), Co(II), Ni(II), Zn(II), Cd(II), and Hg(II) complexes have been synthesized and characterized in the light of microanalytical, IR, H1 NMR, UV-Vis, FAB-mass, ESR, XRD, and TGA spectral studies. The magnetic susceptibility measurements and low conductivity data provide evidence for monomeric and neutral nature of the complexes. On the basis of spectral studies and analytical data, it is evident that the Schiff base acts as tridentate ligand. The Cu(II), Co(II), and Ni(II) complexes were octahedral, whereas Zn(II), Cd(II), and Hg(II) complexes were tetrahedral in nature. The redox behavior of the Cu(II) complex was investigated by electrochemical method using cyclic voltammetry. In order to evaluate the effect of metal ions upon chelation, both the ligand and its metal complexes were screened for their antibacterial and antifungal activities by minimum inhibitory concentration (MIC) method. The DNA cleavage experiment performed using agarose gel electrophoresis method showed the cleavage of DNA by all the metal complexes. The free radical scavenging activity of newly synthesized compounds has been determined at a different concentration range by means of their interaction with the stable free radical 1,1-diphenyl-2-picrylhydrazyl (DPPH).